Toilet Instruments: Symbols of Dissent?. Issue 3 (August 2016) - Crummy, Nina
Summary: A set of mid‐first‐century AD toilet instruments from Silchester includes tweezers in the form of a sheathed sword and a lanceolate nail‐cleaner with iron core. Other tweezers from the same site confirm the set was made by an innovative local smith. Linking the set to the general sword‐ and spear‐shaped forms and indigenous use of nail‐cleaners, the question is raised of how far these small personal items reflected British disaffection immediately after the conquest, and particularly with the disarmament of the Atrebates and other tribes.